War as a Theme in Serbian Periodicals and Literature in the beginning of the XX century – Woman [Жена], Serbian Literary Gazette [Српски књижевни гласник] and war prose by Milica Jankovic and Isidora Sekulic – (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes the war prose by Milica Jankovic and Isidora Sekulic: collections of short stories Unknown Heroes [Neznani junaci] and Waiting [Čekanje], and From the Past [Iz prošlosti]. These collections were written during the wars (1912 –1918) and published shortly after the end of the First World War. The paper points to the social climate and the major ideas that prevailed in the public opinion. The first part of this paper analyzes the war edition of the journal Women [Žena], which is taken as an example magazine with emancipatory feminist tendencies, and the war edition of the Serbian Literary Gazette [Srpski književni glasnik], which is chosen as the main literary magazine of that time. After mapping the concept of war editions of these magazines, this paper analyzes the war prose of selected female authors. It highlights the specific poetics of Milica Janković and Isidora Sekulić, as well as the differences between them.
Keywords: woman and nation; the role of women in war; female solidarity; literary articles; magazine Žena/Woman